Mapping sources of chronic disease-promoting products in retail environments: An analysis of co-location patterns of alcohol, tobacco, and fast-food retailers - Aline D’Angelo Campos; Paul L. Delamater; Marissa G. Hall; Melissa J. Cox; Shelley D. Golden (PLoS ONE, 2026)
Objective High densities of alcohol, tobacco, and fast-food retailers each pose increased risk of behaviors that contribute to chronic diseases. However, retail density studies typically examine only one type of retailer at a time. This study examines co-location patterns of alcohol, tobacco, and fast-food retailers in North Carolina, a geographically and demographically diverse US state. Methods Using 2021 data, we calculated tract-level density of each retailer type (retailers per 1,000 residents) and categorized tracts as “high density” (≥ 75th percentile) or not in each retailer type. We then determined the percentage of residents that lived in tracts high in one, two, three, or none of the retailer types. Additionally, using bivariate logistic regression, we examined the relationship between tracts’ demographic composition and likelihood of being high in all retailer types. Results Among individuals residing in areas with a high density of any retailer type (36.5% of the state’s population), most lived in areas simultaneously high in alcohol, tobacco, and fast-food retailers (9.7%) – exceeding those who lived in areas high in only fast food (9%), only tobacco (4.6%), or only alcohol (3.6%). Areas with a higher percentage of residents below 150% of the federal poverty line, lower median household income, or a larger African American population were more likely to be high in all three retailer types simultaneously (all p < 0.05). Conclusion Our analysis revealed a substantial degree of co-location of alcohol, tobacco, and fast-food retailers, as well as important disparities in the demographic characteristics of the residents in areas where such retailers are more likely to co-locate. This analysis could be expanded to other states, providing insights into reinforcing retail-related risks for chronic diseases and health disparities nationwide.